Robert Adams in Transatlantic Review: Archiving the Barbary Captive and Traveller - Stephen F. Wolfe (European Journal of American Studies)
This paper discusses the reception of a Barbary Coast Captivity Narrative by Robert Adams, published in 1816. The text has often been mentioned in studies of the Barbary Coast narrative but not as a document of a transatlantic discourse about African exploration, ethnography, and colonial development. The creation of Adams text and the creation of the Adams archive will be the subject of the paper as seen by contemporary sources on both sides of the Atlantic. The creation of the Adams narration in the city of London is played off again in the reception of the Adams narrative in Boston. Each set of textual “editors” and reviewers attempt to use the text to intervene in a debate about Timbuctoo, the future of African exploration, and the ways a literary “curiosity” is placed within the aesthetic and ideological needs of emerging discourses of African exploration and racial representation in the first decades of the 19th century on both sides of the Atlantic.